2010
DOI: 10.1007/s11606-010-1383-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Evaluations of Health Care Providers in the Era of Social Networking: An Analysis of Physician-Rating Websites

Abstract: BACKGROUND: Internet-based social networking tools that allow users to share content have enabled a new form of public reporting of physician performance: the physician-rating website. OBJECTIVE: To describe the structure and content of physician-rating websites and to assess the extent to which a patient might find them valuable. METHODS: We searched Google for websites that allowed patients to review physicians in the US. We included websites that met predetermined criteria, identified common elements of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
301
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(320 citation statements)
references
References 9 publications
14
301
2
3
Order By: Relevance
“…33 Although physicians may believe that negative ratings outnumber positive ones on physician-rating Web sites, 34 numerous studies have found that not to be the case. 20,[35][36][37][38][39][40][41][42][43][44] This finding is consistent with what is known about consumer-sourced rating systems in general. In our study, parents reported posting positive ratings for physicians more often than negative ratings, by a factor of 3 to 1.…”
Section: -33supporting
confidence: 83%
See 2 more Smart Citations
“…33 Although physicians may believe that negative ratings outnumber positive ones on physician-rating Web sites, 34 numerous studies have found that not to be the case. 20,[35][36][37][38][39][40][41][42][43][44] This finding is consistent with what is known about consumer-sourced rating systems in general. In our study, parents reported posting positive ratings for physicians more often than negative ratings, by a factor of 3 to 1.…”
Section: -33supporting
confidence: 83%
“…58 Similarly, another study reported that among 33 different rating sites, .70% of physicians did not have a single review on any of the sites. 20 However, the number of physicians with ratings, as well as the number of ratings per physician, is increasing. 38 In addition, it is not clear that this bias and lack of representativeness matters much to parents who may already be familiar with similar issues in ratings of consumer goods such as books and movies.…”
Section: -33mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Few studies have provided quantitative analysis of social media utilization by healthcare organizations or the relationship between end-user metrics and hospital quality and/or outcomes. 11,21,22 However, emerging studies suggest that feedback and ratings on social media and other online rating tools may be correlated with patient satisfaction and objective measures of hospital quality and safety 23 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In addition, social media enables physicians to attract new potential patients, introduce themselves and display their professional accomplishments. 11 In this study, it was found that orthopaedists used social media tools frequently, being Facebook the most popular one with a rate of 73%.…”
Section: Discussionmentioning
confidence: 99%